Development of environmental management framework towards sustainability in oil and gas industry in Libya - Altarog, Abdalrawof (2023)
Energy sources such as gas, oil and coal are significantly used due to worldwide energy consumption. Such use could be increased by 37 per cent in 2035. This increase comes from population growth, reaching 25 % in the next 20 years. In order to apply sustainability systems in these institutions, an account of economically affordable and with minimum impact to the environment and technological viability must be considered. There are stringent regulations and scrutiny in the environment of using oil refining industries to be more sustainable worldwide.